COVID-19 and its effect on emergency presentations to a tertiary hospital with self-harm in Ireland. (30th June 2021) - McIntyre, A.; Tong, K.; McMahon, E.; Doherty, A. M.
Abstract: Objectives: This study aimed to assess the impact of COVID-19 on presentations to an acute hospital with self-harm. Methods: All presentations to University Hospital Galway with self-harm were assessed during the peak period of the coronavirus crisis in Ireland, over the 3 months from 1 March to 31 May 2020. These data were compared with presentations in the same months in the 3 years preceding (2017–2019). Data were obtained from the anonymised service database. Results: This study found that in 2020, the rate of presentation with self-harm dropped by 35% from March to April and rose by 104% from April to May, peaking from mid-May. When trends over a 4-year period were examined, there was a significantly higher lethality of attempt ( p < 0.001), and significant differences in diagnosis ( p = 0.031) in 2020 in comparison with the three previous years. The increased lethality of presentations remained significant after age and gender were controlled for ( p = 0.036). There were also significant differences in the underlying psychiatric diagnoses ( p = 0.018), notably with a significant increase in substance misuse disorders presenting during the 2020 study period. Conclusions: COVID-19 showed a reduction in self-harm presentations initially, followed by a sharp increase in May 2020. If a period of economic instability follows as predicted, it is likely that this will further impact the mental health of the population, along with rates of self-harm and suicidal behaviours. There is a need for research into the longer-term effect of COVID-19 and lockdown restrictions, especially with respect to self-harm.